2022
DOI: 10.3390/su142316045
|View full text |Cite
|
Sign up to set email alerts
|

University Incubator Support and Entrepreneurial Intention among Tourism Graduates: Mediating Role of Personal Attitude

Abstract: The Saudi Arabian government has promoted the tourism industry as a way to achieve the Kingdom’s Vision 2030 by diversifying the economy and reducing overdependence on the oil sector. To align with this, several universities in Saudi Arabia have started providing tourism education. Accordingly, several academic programs and university incubators were launched to prepare workers and entrepreneurs for the industry. This study examines the role of support given by university incubators—embedded in networking supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…This could be done through training and development programs [92]. Business incubators at universities can play this role by developing students' capabilities, enhancing their skills and self-confidence, and stimulating their attitude towards investment, which would affect their entrepreneurial and investment intention [93]. Further research could replicate the current study model with a larger sample size to validate or falsify our results.…”
Section: Implications Of the Studymentioning
confidence: 77%
“…This could be done through training and development programs [92]. Business incubators at universities can play this role by developing students' capabilities, enhancing their skills and self-confidence, and stimulating their attitude towards investment, which would affect their entrepreneurial and investment intention [93]. Further research could replicate the current study model with a larger sample size to validate or falsify our results.…”
Section: Implications Of the Studymentioning
confidence: 77%
“…Hence, understanding the factors that affect their GEI is essential. The current research showed that to create GEI, university education systems, including university incubators (Aliedan et al 2022;Ayad et al 2022), must promote environmental information and knowledge among university students. Workshops and training sessions on environmental issues are encouraged, since they can enhance students' environmental knowledge and ESI.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
“…Another study [43] found a significant effect of investment awareness on investment intention. This investment knowledge of graduates is shaped by university education support [23,24]. A recent study [17] found that knowledge of green investment is a predictor of green investment among university students in Malaysia.…”
Section: Green Consumption Commitment Green Knowledge Green Investmen...mentioning
confidence: 99%
“…The current study adopts TPB for understanding investment intention among university graduates in a green context. TPB framework has been adopted for examining human behaviour in different contexts, such as entrepreneurial intention among higher education [23,24], food waste intention [25], excessive food buying [26], fast food buying intention [27], healthy food item choices [28], state-branded food product purchase [29], or consumer behaviour regarding organic menus [30].…”
Section: Theory Of Planned Behaviour and Green Investmentmentioning
confidence: 99%